Mengelola Keuangan UMKM Toko Sembako Sumber Rezeki - Tanya Tata Putri Srikandi; Elfalina Magymai; Widya Kusuma Wardani; Rosaidina Syafira; Nicho Candra Hariyanto Putra; Sri Rahayuningsih (Jurnal Riset Akuntansi, 2024)
Standard Accounting for Micro, Small and Medium Entities (SAK EMKM) is a financial accounting standard specifically designed to meet the financial reporting needs of micro, small and medium enterprises (MSMEs) in Indonesia. This research is designed to produce a simple financial report format based on SAK EMKM for MSMEs so that it is easy to understand and apply by micro, small and medium entities that generally have limited human and financial resources. Toko Sumber Rezeki as a medium-sized business in the field of grocery trading also needs SAK EMKM. This aims to help prepare financial reports that are relevant, reliable, and easy to understand, so as to improve the transparency, accountability, and competitiveness of the business. This research uses a qualitative descriptive approach and the data collection techniques used are interviews and literature studies. From the results of the research conducted, it can be concluded that the financial statements of Toko Sumber Rezeki have not been able to apply SAK EMKM because their financial records are only in the form of simple cash expenditure and receipt records. Management strategies will be applied to determine the profit or loss of the Micro, Small and Medium Enterprises Toko Sumber Rezeki, one of which is the petty cash financial transaction procedure.